GAMBARAN KONSEP DIRI PENYANDANG DISABILITAS FISIK TUNA DAKSA YANG BEKERJA - Natanael, Efraim David; Wibawa, Dhevy Setya (MANASA, 2024)
Work is essential for fulfilling life's needs, including for physically disabled individuals. These individuals have significant opportunities in the workforce, supported by government initiatives aimed at enabling their employment. Despite this support, their participation remains low due to internal and external factors. Internal factors include a low self-concept, while external factors involve a work environment that is not accommodating to people with disabilities.This research aims to provide an overview of self-concept and the factors influencing the self-concept of physically disabled individuals working in government companies. A qualitative approach with narrative methods was used, involving semi-structured interviews conducted twice. Thematic analysis was employed to analyze the data.The results indicated that all three participants had a positive self-concept. They accepted their life conditions and maintained realistic expectations based on their abilities. Influential factors shaping their self-concept included support from parents and friends. Additionally, age differences were found to be a differentiating factor.